2009
DOI: 10.1186/ar2845
|View full text |Cite
|
Sign up to set email alerts
|

Dual energy x-ray absorptiometry analysis contributes to the prediction of hip osteoarthritis progression

Abstract: IntroductionTo determine if structural bone parameters obtained from dual energy X-ray absorptiometry (DXA) contribute to the prediction of progression of hip osteoarthritis (OA) and to test if the difference between the most affected (OA) hip and the contralateral hip adds to this prediction.MethodsThe study group involves a prospective cohort of 189 patients that met the American College of Rheumatology (ARC) classification criteria for hip osteoarthritis. Progression was defined as 20% joint space narrowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Previous studies have found increased BMD and differences in DXA‐derived geometry values in OA hips as compared to controls without OA (19, 35–38). However, the majority of those studies used the classic definition of hip OA, which required the presence of cartilage degradation (joint space narrowing) and osteophytes.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have found increased BMD and differences in DXA‐derived geometry values in OA hips as compared to controls without OA (19, 35–38). However, the majority of those studies used the classic definition of hip OA, which required the presence of cartilage degradation (joint space narrowing) and osteophytes.…”
Section: Discussionmentioning
confidence: 86%
“…No difference in spine BMD was seen in women whose osteophytes or joint space width progressed compared with osteoarthritis non-progressors 6. By contrast, the GOAL trial demonstrated that patients with hip osteoarthritis progression had a higher bone mineral content in certain regions of the femoral head compared with non-progressing patients 37. Furthermore, a twin study showed an inverse relationship between osteoarthritis and osteoporosis at the osteoarthritis-affected hip, but no association was found between hip osteoarthritis and BMD at the contralateral site, lumbar spine, or total body 38…”
Section: Established Osteoarthritis: Cartilage Damage/increased Subchmentioning
confidence: 93%
“…Although an extensive amount of literature shows an inverse relationship between osteoarthritis progression and osteoporosis,79 12 14 15 18 37 38 other studies did not reach the same conclusions 29 39. In addition, low hip BMD has been weakly related to knee osteoarthritis progression as assessed by osteophyte growth,6 while this association was not evident in those whose JSN had progressed 6 13.…”
Section: Established Osteoarthritis: Cartilage Damage/increased Subchmentioning
confidence: 96%
“…Given the previous results showing that FSA can be applied on hip radiographs [22] and that bone density related parameters from dual energy X-ray absorptiometry (DXA) contribute to the risk and progression of hip OA [23][24][25][26], we hypothesize that radiography-based bone texture gives additional information in predicting the development of radiographic hip OA (rHOA). Consequently, our aim was to create a method for automated assessment of bone texture in proximal femur and acetabulum from plain hip radiographs and to assess the ability of these bone texture parameters to predict incident rHOA.…”
Section: Introductionmentioning
confidence: 98%